A deep learning based autonomous electric vehicle on unstructured road conditions - Adnan, Ashik; Rahman, G M Mahbubur; Hossain, Md. Mahafuj; Mim, Mahfuza Sultana (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.